2009
DOI: 10.1093/hmg/ddp306
|View full text |Cite
|
Sign up to set email alerts
|

Rare pathogenic microdeletions and tandem duplications are microhomology-mediated and stimulated by local genomic architecture

Abstract: Genomic copy number variation (CNV) plays a major role in various human diseases as well as in normal phenotypic variability. For some recurrent disease-causing CNVs that convey genomic disorders, the causative mechanism is meiotic, non-allelic, homologous recombination between breakpoint regions exhibiting extensive sequence homology (e.g. low-copy repeats). For the majority of recently identified rare pathogenic CNVs, however, the mechanism is unknown. Recently, a model for CNV formation implicated mitotic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
172
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 151 publications
(191 citation statements)
references
References 53 publications
15
172
4
Order By: Relevance
“…This indicates the absence of rearrangement hotspots, which is in line with previous findings (Beysen, et al, 2005;D'haene, et al, 2009;Shaw and Lupski, 2004). These nonrecurrent rearrangement events are suggestive of nonhomologous end joining (NHEJ), alternative NHEJ (alt-NHEJ), or Fork Stalling and Template Switching (FoSTeS) as possible underlying mechanisms (Lee, et al, 2007;Shaw and Lupski, 2004;Vissers, et al, 2009). Noteworthy, we recently proposed a mechanism that triggered the generation of a deletion upstream of FOXL2 in a patient with BPES (D 'haene, et al, 2009).…”
Section: Discussionsupporting
confidence: 90%
“…This indicates the absence of rearrangement hotspots, which is in line with previous findings (Beysen, et al, 2005;D'haene, et al, 2009;Shaw and Lupski, 2004). These nonrecurrent rearrangement events are suggestive of nonhomologous end joining (NHEJ), alternative NHEJ (alt-NHEJ), or Fork Stalling and Template Switching (FoSTeS) as possible underlying mechanisms (Lee, et al, 2007;Shaw and Lupski, 2004;Vissers, et al, 2009). Noteworthy, we recently proposed a mechanism that triggered the generation of a deletion upstream of FOXL2 in a patient with BPES (D 'haene, et al, 2009).…”
Section: Discussionsupporting
confidence: 90%
“…However, a common HERVH element is present at both sides of the deletion for both patients. Recently Vissers et al 9 indicated that rare pathogenic CNVs do not seem to occur in random genomic sequences, but may favor locations with a high content of specific architectural features. The presence of this microhomology at the break-point junctions in patients 2 and 3 is suggestive for a microhomology-mediated rearrangement.…”
Section: Discussionmentioning
confidence: 99%
“…For the validation of the CNVs by independent molecular methods, we established CNV-specific PCRs with primers located near the presumptive breakpoints, as described by Vissers et al 18 Primers located in the 5 0 and 3 0 flanking sequences outside of a large deletion allow proof of existence of the deletion and identification of the deletion breakpoints (Supplementary Material 2). Duplications were validated with primers at the 3 0 (forward) and 5 0 (reverse) ends within the duplication in order to amplify the joining of the 3 0 end and the 5 0 end of two tandem copies.…”
Section: Molecular Characterization Of Cnvsmentioning
confidence: 99%